Paradigms and Philosophical Foundations of Islamic Religious Education Research: A Literature Review of Quantitative, Qualitative, and Mixed Methods Approaches - Anisa Siti Nurhaliza; Farid Abdul Majid; Maryam Dwi Lestari; Sinta Niasti; Ayu Aprianti; Bayu Bambang Nur Fauzi (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the paradigms and philosophical foundations of Islamic Religious Education (PAI) research and their relationship with quantitative, qualitative, and mixed methods approaches. This research employed a literature review method by examining books, scientific journals, and relevant academic sources. The findings indicate that positivism is closely related to quantitative research, while post-positivism and constructivism provide the philosophical basis for qualitative research. Mixed methods integrate the strengths of both approaches to produce a more comprehensive understanding of research problems. The study concludes that understanding research paradigms is essential for determining appropriate methods and producing valid and relevant PAI research.